2015
DOI: 10.14488/1676-1901.v15i2.1936
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento, condução e análise do método de avaliação de uma disciplina do curso de engenharia de produção fundamentada na aprendizagem baseada em problemas

Abstract: Resumo: Em um mercado altamente competitivo, as empresas necessitam de recursos humanos cada vez mais qualificados, em especial no que se refere à Engenharia. As Universidades desempenham, pois, um papel importante, ao formar os futuros profissionais do país. No entanto, nesta tarefa, as Instituições deparam-se com o desafio de atrair e trabalhar com jovens da Geração Y, que apresentam anseios não mais atendidos apenas pelos métodos tradicionais de ensino. A Aprendizagem Baseada em Problemas (ABP) é uma aborda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…I was really interested in the case, I think the only difficulty was getting the team to agree on an idea, just because of this divergence of thought, but after we reached a consensus, everything went smoothly. (I3.4) Teamwork was also identified as a challenging factor in a study on the use of PBL by Pinto et al (2015). The authors found that some groups had problems with leadership, as some members were resistant to respecting the established hierarchy, including the roles and responsibilities of each member, which overburdened the members who were more responsible and committed to the course.…”
Section: Factors That Facilitate and Limit Learning In The Adoption Omentioning
confidence: 99%
See 1 more Smart Citation
“…I was really interested in the case, I think the only difficulty was getting the team to agree on an idea, just because of this divergence of thought, but after we reached a consensus, everything went smoothly. (I3.4) Teamwork was also identified as a challenging factor in a study on the use of PBL by Pinto et al (2015). The authors found that some groups had problems with leadership, as some members were resistant to respecting the established hierarchy, including the roles and responsibilities of each member, which overburdened the members who were more responsible and committed to the course.…”
Section: Factors That Facilitate and Limit Learning In The Adoption Omentioning
confidence: 99%
“…A third role can be integrated into the processthe ambassador, a tutor who is active in the business world and involved in the studied activity. Such tutors are generally employees who work directly in areas related to the proposed problem and can provide useful information about the topic (Pinto et al, 2015).…”
Section: 1mentioning
confidence: 99%
“…A avaliação é realizada ao final do processo e responsabiliza os estudantes pela reflexão sobre o próprio aprendizado, não focando apenas na avaliação do professor (Pinto et. al, 2015).…”
Section: Figura 1 | Etapas Aprendizagem Baseada Em Problemasunclassified
“…O mundo contemporâneo, configurado como a era do conhecimento, apresenta um cenário de competição entre as organizações, pressionando-as a desenvolver e manter: acesso a recursos e tecnologias; domínio técnico para produzir com eficiência e qualidade; Já para Pinto et al (2015), a aprendizagem baseada em problemas é:…”
Section: Introductionunclassified